A New “Business as Usual” Climate Scenario and the Stress Response of the Caribbean Coral Montastraea cavernosa - Lesser, Michael P.; Jarett, Jessica K.; Fiore, Cara L.; Thompson, Megan M.; Pankey, M. Sabrina; Macartney, Keir J. (Frontiers in Marine Science, 2020)
The climate change related decline of shallow (<30 m) coral reef ecosystems has been driven by the significant mortality of scleractinian corals caused primarily by the phenomenon known as “coral bleaching”. Despite pervasive phase shifts and macroalgal dominance on many coral reefs some coral species have persisted on many reefs. One of those species is Montastraea cavernosa which has been categorized as resilient to a range of biotic and abiotic insults. Here we present the results of a thermal stress and ocean acidification experiment on M. cavernosa, both its brown and orange color morphs, closely representing predictions from the Representative Concentration Pathway (RCP) 6.0 scenario in the year 2100. We assessed the community response of the microbiome, and the molecular responses of critical pathways in the host by quantifying transcript abundances of genes encoding fluorescent proteins, heat shock proteins, antioxidant enzymes and regulators of apoptosis. After a 12 d acclimatization experiment no visible bleaching was observed in any treatment, and the excitation pressure on photosystem II of the symbiotic Symbiodiniaceae, while lower under the combined effects of thermal stress and ocean acidification, was not significantly different than control samples. Only minor, but significant, changes in the prokaryotic microbiome were observed when exposed to RCP 6.0 predicted ocean acidification conditions. At the end of the experiment, the host heat shock protein 90 (HSP 90) showed an increase in transcript abundance under the interactive effects of thermal stress and ocean acidification compared to high temperatures alone, but these treatment groups were not significantly different than treatments under normal temperatures. While Bax, an activator of apoptosis, was significantly higher under thermal stress alone compared to control samples. Taken together, M. cavernosa, exhibits persistence, resistance and resilience generally, and when experimentally exposed to the more realistic RCP 6.0 climate model conditions.